(untitled) (Semiárida, 2020)
We analyzed the content of phosphorus (P), calcium (Ca), magnesium (Mg), total ash (Cen) and insoluble ash (Insol), iron (Fe), copper (Cu) and zinc (Zn) in forage species growing wild in silvopastoral system of the Lower Delta of the Parana River after planting forest. 10 plants were harvested from the following species: Glyceria multiflora (Cebadilla de agua), Deyeuxia viridiflavescens (Pasto plateado), Melilotus officinalis (Trébol de olor amarillo), Phalaris angusta (Alpistillo), Lolium multiflorum (Ray gras), Lathyrus pubescens (Arvejilla), Vicia gramínea (Vicia) y Leersia hexandra (Arrocillo). They were dried, incinerated and ashes dissolved in acid. Mineral determinations were performed by atomic absorption spectrophotometry (AAS) and colorimetry. Mineral contents in the species studied here were lower than values informed previously of forage species of temperate weather and, in some cases, mineral requirements for cattle.